The Use of Islamic History Videos through Swell Strategy to Improve Senior High Students’ Narrative Writing Achievement - JUNA WARNI (Edukasi, 2018)
The objectives of this study were to find out: (1) whether or not there was a significant improvement on students’ narrative writing achievement between before and after the students were taught by using Islamic history videos through SWELL Strategy, and (2) whether or not there was a significant difference on students’ narrative writing achievement between the students who were taught by using Islamic history videos through SWELL Strategy and those who were not. The population of this study was all the eleventh grade students of Senior High School Nurul Iman Palembang which consisted of 65 students. The sample of this study was taken by using total sampling. Thus, the total number of the sample was 65 students. The sample was XI Science class (control group) which consisted of 33 students and XI Social Science class (experimental group) which consisted of 32 students. In collecting the data, written test was used. The test was given twice to both experimental and control group, as a pretest and posttest. To verify the hypotheses, the data of students’ pretest and posttest of both groups were analyzed by using paired sample t-test and independent sample t-test in SPSS. The findings showed that the p-output (sig 2-tailed) from paired sample t-test was 0.000 which was lower than 0.05, and the t-value 7.954 which was higher than t-table 2.040 (with df= 31). Then, p-output from independent sample t-test was 0.021 which was lower than 0.05, and t-value 2.371 which was higher than t-table 1.998 (with df= 63). Therefore, it could be inferred that narrative writing by using Islamic history videos through Social-Interactive Writing for English Language Learners (SWELL) Strategy gave significant improvement on the students’ narrative writing achievement, and gave significant difference between students’ who were taught by using Islamic history videos through SWELL Strategy and those who were not.